A permanência e a ruptura : arte e política em Hannah Arendt. - Silva, Cícero Samuel Dias (2013)
This thesis investigates the relationship between art and politics in Hannah Arendt’s thought. The objective is to present the way the issue is viewed by the author. To achieve this end, concepts of rupture and permanece will be articulated. Therefore, it resorts to such works as The Human Condition (1951), Between Past and Future (1968), Men in Dark Times (1968) and The Life of the Mind (1978), inasmuch as these writings seem to condense fundamental traces of this discussion, given as effective means of aproximation to this problem. The first chapter focuses on the analysis of the general environment from which Arendt composes its reflexive web, ie: that one consisting on political issues that emerge in the events of the twentieth century. One diagnoses a broad context of crisis drawn from the understanding of an undeniable fraying of Western moral and political tradition. When the traditional political and moral categories that guide action and thought are broken, one experiences the radical inability to judge, linked to the inaccessibility of the past that reverberates in the very opacity of the present. Before the confirmation of a crisis given as a synonym for the darkening of the world, to which art and politics - dimensions par excellence ruled in permanence - do not pass unscathed, one moves to a second chapter whose reflection adheres to the idea of culture in the face of the lost of tradition; one travels up the topic of culture in a mass society, linking it to concepts like philistinism and entertainment. Taking the breaking theme, chained by the preceding chapters, the third chapter highlights the rehabilitation of appearence as able to demonstrate the relationship between contemporary art and politics, coming thus to the core point of our proposal.